2019
DOI: 10.1002/ldr.3434
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal changes of permafrost in the Headwater Area of the Yellow River under a changing climate

Abstract: This article attempts to predict the spatiotemporal changes of permafrost in the Headwater Area of the Yellow River (HAYR) on the northeastern Qinghai‐Tibet Plateau, Southwest China by using field monitoring and numerical models. Permafrost in the HAYR is categorized into four types: low‐ and high‐ice‐content high‐plain permafrost and low‐ and high‐ice‐content alpine permafrost. According to these permafrost types, changes in permafrost temperature were calculated by coupling a geometric model with the soil th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…An increased baseflow and melting ground-ice would boost groundwater recharge and increase groundwater storage upon permafrost thaw (e.g., [10,[18][19][20][21][22][23]). With a catchment area of 21,000 km 2 , the Headwater Area of the Yellow River (HAYR, above the Huanghe'yan Hydrological Station) on the northeastern Qinghai-Tibet Plateau (QTP), with widespread discontinuous (~86%) permafrost [24][25][26], and under a persistently warming and slightly wetting climate, flow regimes of the Yellow River in the HAYR have shown no evident increasing trend in general as reported. Instead, the Yellow River flow showed a general trend of decline during 1955-2019, but the ratio of the Q Max /Q Min demonstrated a slightly increasing trend under permafrost degradation, in contrast to the observed streamflow shifts in other northern and alpine permafrost regions (e.g., [6,7,13,19]).…”
Section: Introductionmentioning
confidence: 94%
“…An increased baseflow and melting ground-ice would boost groundwater recharge and increase groundwater storage upon permafrost thaw (e.g., [10,[18][19][20][21][22][23]). With a catchment area of 21,000 km 2 , the Headwater Area of the Yellow River (HAYR, above the Huanghe'yan Hydrological Station) on the northeastern Qinghai-Tibet Plateau (QTP), with widespread discontinuous (~86%) permafrost [24][25][26], and under a persistently warming and slightly wetting climate, flow regimes of the Yellow River in the HAYR have shown no evident increasing trend in general as reported. Instead, the Yellow River flow showed a general trend of decline during 1955-2019, but the ratio of the Q Max /Q Min demonstrated a slightly increasing trend under permafrost degradation, in contrast to the observed streamflow shifts in other northern and alpine permafrost regions (e.g., [6,7,13,19]).…”
Section: Introductionmentioning
confidence: 94%
“…In the HAYR, discontinuous, isolated, and sporadic permafrost presents and account for 86% of the catchment area above HHY near Madoi (Li et al, 2016;Wang et al, 2018;Sheng et al, 2020). Mean annual ground temperatures, generally measured at 10-25 m in depth, are higher than -2.0 ; permafrost thickness in the HAYR is generally less than 73 m according to borehole measurements (Luo et al, 2012), and; the average active layer thickness (ALT) in the HAYR varies from 1.8 -2.4 m (1980-2006) (Luo et al, 2014).…”
Section: Study Areamentioning
confidence: 99%
“…In recent decades, the HAYR has witnessed a marked climate warming and subsequent permafrost degradation (Jin et al, 2009(Jin et al, , 2011Luo et al, 2018). The ALT has increased at a rate of 1.2 cm yr -1 (1972-2012), and; by 2100, the ALT is projected to increase by 2.78-4.39 m and permafrost areal extent in the HAYR is projected to decrease by 7.5%-8.6% under varied carbon emission scenarios (Sheng et al, 2020).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The research of Duan et al (2021) on the relationship between the normalized difference vegetation index and climate change shows that different vegetation types on the Qinghai‐Tibet Plateau have great spatial differences in response to climate change. Through field testing and numerical simulation, Sheng et al (2020) found that the area of permafrost on the Qinghai‐Tibet Plateau decreased by more than 1000 km 2 due to the sharp rise in temperature after 1980, and the problem of desertification has become increasingly serious. In addition, the continuous distribution of the landscape index is of great significance to the environment of the biological community.…”
Section: Introductionmentioning
confidence: 99%